Equate access to primary health care in rural Kalimantan: what essential health services should be available locally? - Ferry Fadzlul Rahman; Fahni Haris; Kellyana Irawati (Journal of Holistic Nursing Science, 2023)
Indigenous and remote ethnic populations experience poorer health status than metropolitan populations due to unequal access to essential healthcare services (Primary healthcare). This study aims to assess which essential health services are best provided by health workers and describe the service needs problem from the patient's perspective. The Delphi method consists of informants represented by rural and remote health centers. Using open-ended questions, they represent the population for each health center service. Each question must identify a problem based on the core of essential health services. The results of the study show that the criteria that must be met include the importance of equality in health services; consideration of social determinants of health; flexibility, effective resource budgeting, adjusting the type of health services according to patient needs, and providing assistance as close to home as possible. The conclusions of this study can help policymakers and service planners to determine what types of service needs should be provided by health workers in remote areas, to allocate resources and provide services more equitably, and to inform patients about healthcare services that they expect to be able to access pretty within the community. Keywords: Health care system; community nursing; nursing care; delphi study; health population